A Case of Hair Thread Torniquet Syndrome in a Neonate - Unusual Hand Injury Caused by Mittens - Rabindran Chandran; Hemant Parakh (International Journal of Medical Research and Review, 2015)
Hand injury secondary to mittens application have been reported since 1960s. A neonate was brought with history of bilateral hand swelling with dusky discoloration predominantly involving the right hand. Two mittens were worn in both hands and tightened at the wrist by elastic bands. Discoloration of the right hand with constriction mark at the wrist was noted. Hair thread tourniquet syndrome was suspected which is caused by hair or synthetic strands tightly wrapped around appendages.The underlying pathophysiology is impedance of lymphatic flow, venous outflow and/or arterial inflow obstruction. Treatment is prompt removal of the constricting substance with supportive care.